Understanding trade union usage of social media: A case study of the Public and Commercial Services union on Facebook and Twitter. (29th July 2021) - Houghton, David J.; Hodder, Andy
Abstract: This paper provides the first cross‐platform examination of trade union social media posts, focussing on the online content of the Public and Commercial Services (PCS) union. Data scraped from the union's Facebook posts ( n  = 282) were compared with data obtained from the union's Twitter account ( n  = 1554) to investigate the extent to which social media reflects a union's identity and utilises the language of mobilisation theory to engage with their audience. Across a six‐month period (July–December 2019), findings demonstrated PCS behaved in an interactive manner on social media, avoiding the pitfalls of a 'bulletin board' approach through using the language of mobilisation theory. However, content was engaged with users to different extents depending upon which platform the content was posted. Findings also suggest that social media posts can reflect a version of union identity.